Water in Eclogite and Pyroxenite Xenoliths From the Bottom 100 km of the Slave Craton (Canada) Mantle Root - Schmädicke, Esther; Gose, Jürgen; Stachel, Thomas (Geochemistry Geophysics Geosystems, 2025)
Major and trace elements, including H2O, were determined in garnet and clinopyroxene to constrain the evolution of mantle xenoliths from Diavik, Canada. The 20 samples, derived from 120 to 220 (240) km depth, define a geotherm equivalent to 37 mW/m2 surface heat flow and include three eclogite (A, B, C) and two pyroxenite (B, C) types (A: High Ca/low Mg, B: High Ca/high Mg; C: Low Ca/high Mg). C-type samples invariably come from lower depth (<175 km) than B-types (>200 km); type-A eclogite is present in both intervals. The contents of hydroxyl (referred to as “structural H2O” and given as μg/g H2O) in clinopyroxene of B-type eclogite and pyroxenite (360–1,149 and 225–1,509 μg/g) are higher than in C-type samples (123–165 and 321–393 μg/g). Moreover, clinopyroxene in eclogite has lower H2O contents relative to pyroxenite. Structural H2O of clinopyroxene is positively correlated to Cu, Ni, and K but not to major elements. In garnet, contents of structural H2O are low (0–41 μg/g) and correlate neither with rock type nor with mineral composition. Most garnets additionally contain molecular (non-structural) water, being correlated to compositional parameters of both garnet (positive: Mg; negative: Ca, Sr, Be, Na) and clinopyroxene (positive: MREE, Ca, Th; negative: Al, K, Na, Li). Structural H2O in clinopyroxene and garnet does not correspond to PT conditions but was affected by secondary, metasomatic processes. Most likely, pyroxenite formed from eclogite by metasomatic changes resulting in lower clinopyroxene Na and Zn contents and enhanced Mg#, Cr, Sr, REE, Pb, Th, U, and Cu.
CRIS-Team Scopus Importer:2025-03-28
Keywords: Diavik; eclogite; H; nominally anhydrous minerals; pyroxenite; slave craton